Cushing’s syndrome with no clinical stigmata – a variant of glucocorticoid resistance syndrome - Ved V. Gossain; Mohammad El-Rifai; Preethi Krishnan; Bhavini Bhavsar (Clinical Diabetes and Endocrinology, 2018)
Abstract Background Cortisol resistance syndrome is a very rare condition characterized by high cortisol levels, but without any clinical features of Cushing’s syndrome. Our objective is to present such a case. Case presentation A 41 year old female presented with mild hirsutism and elevated urinary cortisol levels. Plasma cortisol levels were elevated and were not suppressed by conventional doses of dexamethasone on multiple occasions, but decreased following administration of higher doses of dexamethasone. Adrenocorticotropic hormone (ACTH) levels were inappropriately elevated. Despite significantly elevated cortisol levels, she did not develop any clinical signs or symptoms of Cushing’s syndrome. Pituitary and adrenal imaging did not reveal any abnormalities. Genetic testing for human glucocorticoid receptor did not reveal any mutations. Conclusions Although we were not able to identify any new mutations, we believe that our patient has a variant of cortisol resistance syndrome. This syndrome should be considered in the differential diagnosis of patients who present with high levels of cortisol but have no clinical features of Cushing’s syndrome.